Alu repeats as transcriptional regulatory platforms in macrophage responses to M. tuberculosis infection. Issue 22 (6th September 2016) - Bouttier, Manuella; Laperriere, David; Memari, Babak; Mangiapane, Joseph; Fiore, Amanda; Mitchell, Eric; Verway, Mark; Behr, Marcel A.; Sladek, Robert; Barreiro, Luis B.; Mader, Sylvie; White, John H.
Abstract: To understand the epigenetic regulation of transcriptional response of macrophages during early-stage M. tuberculosis (Mtb) infection, we performed ChIPseq analysis of H3K4 monomethylation (H3K4me1), a marker of poised or active enhancers. De novo H3K4me1 peaks in infected cells were associated with genes implicated in host defenses and apoptosis. Our analysis revealed that 40% of de novo regions contained human/primate-specific Alu transposable elements, enriched in the AluJ and S subtypes. These contained several transcription factor binding sites, including those for members of the MEF2 and ATF families, and LXR and RAR nuclear receptors, all of which have been implicated in macrophage differentiation, survival, and responses to stress and infection. Combining bioinformatics, molecular genetics, and biochemical approaches, we linked genes adjacent to H3K4me1-associated Alu repeats to macrophage metabolic responses against Mtb infection. In particular, we show that LXRα signaling, which reduced Mtb viability 18-fold by altering cholesterol metabolism and enhancing macrophage apoptosis, can be initiated at response elements present in Alu repeats. These studies decipher the mechanism of early macrophage transcriptional responses to Mtb, highlighting the role of Alu element transposition in shaping human transcription programs during innate immunity.